Utility of Carpal Tunnel Release and Ulnar Decompression in CMT1A and HNPP. Issue 4 (11th August 2022) - Chompoopong, Pitcha; Niu, Zhiyv; Shouman, Kamal; Madigan, Nicolas N.; Sandroni, Paola; Berini, Sarah E.; Shin, Alexander Y.; Brault, Jeffrey S.; Boon, Andrea J.; Laughlin, Ruple S.; Thorland, Erik; Mandrekar, Jay; et al.
Abstract: Introduction/Aims: Carpal and cubital tunnel syndrome (CTS, CuTS) are common among patients with hereditary neuropathy with liability to pressure‐palsies (HNPP) and Charcot–Marie‐Tooth type 1A (CMT1A) and may impact quality of life. We aimed to evaluate the utility of nerve decompression surgeries in these patients. Methods: Medical records were reviewed for patients with PMP22 mutations confirmed in Mayo Clinic laboratories from January 1999 to December 2020, who had CTS and CuTS and underwent surgical decompression. Results: CTS occurred in 53.3% of HNPP and 11.5% of CMT1A, while CuTS was present in 43.3% of HNPP and 5.8% of CMT1A patients. CTS decompression occurred in 10‐HNPP and 5‐CMT1A patients, and CuTS decompression with/without transposition was performed in 5‐HNPP and 1‐CMT1A patients. In HNPP, electrodiagnostic studies identified median neuropathy at the wrist in 9/10 patients and ultrasound showed focal enlargements at the carpal and cubital tunnels. In CMT1A, median and ulnar sensory responses were all absent, and the nerves were diffusely enlarged. After CTS surgery, pain, sensory loss, and strength improved in 4/5 CMT1A, and 6/10 HNPP patients. Of clinical, electrophysiologic and ultrasound findings, only activity‐provoked features significantly correlated with CTS surgical benefit in HNPP patients (odds ratio = 117.0:95% confidence interval, 1.94 > 999.99, p = 0.01). One CMT1A and one HNPP patient improved with CuTS surgery while 2 HNPP patients worsened. Discussion: CTS symptom improvement post‐surgery can be seen in CMT1A and (less frequent) in HNPP patients. CuTS surgery commonly worsened course in HNPP. Activity‐provoked symptoms in HNPP best informed benefits from CTS surgery.